PSYCHOTROPIC DRUGS-II - Mallik, Utpal (SCHOOL SCIENCE, 2013)
Most of the drugs we are going to talk about now are synthetic products. Hoffman, a Swiss chemist, was working on substances derived from the argot fungus and quite accidentally found out that argot contains lysergic acid, the precursor of now well-known LSD. The term LSD has been derived from the German term for D-lysergic acid dimethylamide 15—a strong hallucinogenic compound. The discovery of lysergic acid stimulated its medical use as a therapeutic aid. Its subsequent success in medical use may be doubted, but LSD was promptly picked up by drug-takers. Colourless, odourless and tasteless, LSD is one of the most widely used drugs today. Easy to manufacture and distribute. LSD is taken orally or sniffed or even injected into the body (in the form of solution). It is available in capsules or tablets, often mixed with food items, to hide it from public notice. In the Western countries, one of the common methods of passing around LSD is mixing it with the gum of postage stamps—a little amount provides a full reaction.